แบบจำลองสมดุลทางความร้อนเคมีของเตาผลิตแก๊สเชื้อเพลิงจากถ่านหินสำหรับเตาอุตสาหกรรม - นริศ วงศ์ทยานุวัตร (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This research studies mathematical modeling of coal gasification for industrial steel reheating furnace. This model employs the principle of thermochemical to predict the final composition and heating value of producer gas, reaction temperature, cold gas efficiency and second low efficiency. Coal represented as CHαOβNγSθ reacts with air and steam to produce gasification products containing CO, CO₂, H₂, CH₄, H₂O, N₂ and SO₂. The parameters of interest in this study are air to coal ratio, moisture content in coal, steam to coal ratio and coal composition. This model is a useful tool for analysis and design of coal gasifier including its control conditions. In case of Indominco coal, the obtained results show that the principle of thermochemical well explain the gasification which RMSE is lower than 2.5. The maximum heating value is reached when solid carbon has been already converted. At air to coal ratio of 2.6 to 3.3, the coal gas efficiency is exhibited more than 70% and the heating value of producer gas is between 17.5 to 20 MJ/Kg coal. Therefore if producer gas is used in place of fuel oil for 50 ton/hr steel reheating furnace, saving of 20,957 to 22,551 baht/hr may be realized (for prices of coal and fuel oil are 3.56 Baht/kg and 22.47 Baht/liter respectively). The payback period is no more than 13 months.